'I don't want to think about it': Psychosocial experiences of road traffic accident survivors in Ghana. (November 2020) - Wilson, Priscilla; Dzansi, Gladys; Ohene, Lilian Akorfa
Highlights: Road traffic accident survivors suffer different psychological consequences. The immediate reactions of road traffic accident survivors are affected by their own experiences and the care received. Emotional numbing, resentment and anxiety are common reactions among trauma survivors that require collaborative management. Social life is affected by role changes and perceive sense of acceptance or rejection. Holistic periodic assessment of road traffic accident survivors will enhance effective management. Abstract: Introduction: Road traffic injuries are among the top ten traumatic events that affect the psychosocial wellbeing and quality of life of survivors. The aim of this study was to explore the experiences of road traffic accident survivors in Ghana, a low-middle-income country in sub-Saharan Africa. Methods: The study adopted an interpretive qualitative research design. Thirteen (13) participants were purposively selected from the Accident Centre of the largest public teaching hospital in Ghana. Data collection employed in-depth face-to-face interviews using a semi-structured guide. Data analysis occurred concurrently using thematic analysis methods. The right to participate or withdraw from study was protected. Findings: Three major themes deductively generated from the research were cognitive experiences, affective responses and social experiences of Road Traffic Accident survivors. Nearly all survivors of road traffic accidents experience repetitive episodes of intrusive thoughts, nightmares, anxiety and other extreme emotions suggesting post-traumatic stress, which is often unrecognized. Conclusion: Immediate reactions of survivors of road traffic accident are affected by their experiences, accessibility of support, and the responses of the larger community. We propose that a focused assessment and management of accident survivors for post-traumatic disorder be included in existing care modalities to promote a holistic care and recovery for survivors.